Technological Rationality in Five Coastal Communities of Newfoundland: Historical and Contemporary Challenges to Lifelong Learning - Carol E. Harris; Darlene E. Clover (Adult Education Research Conference, 2004)
The introduction of information and communication technologies into five coastal sites in Newfoundland offers both promise and challenge to a people struggling in the wake of the collapse of their single resource, the cod fishery. Our study asks again Heidegger’s question about technology: in what manner does it affect one’s very way of Being?